Strengthening Village Governance Through Technical Assistance In The Preparation Of Village Regulations In Dongi Village, Sidenreng Rappang Regency - Muhammad Zulfan Hakim; Eka Merdekawati Djafar; Tri Fenny Widayanti; Fajlurrahman Jurdi; Naswar (STMIK Indonesia Banda Aceh, 2026)
The gap between village and city regulations causes differences in the quality of government administration, especially due to the limited understanding of village officials in drafting appropriate and harmonious regulations. This article aims to strengthen village governance in Dongi Village, Sidenreng Rappang Regency through technical assistance in the preparation of village regulations. This study uses a descriptive method to provide a systematic and factual picture of the challenges faced by the village government, supported by literature studies and interviews with the community. The findings of the study show that low legal literacy, limited technical skills, and lack of community participation are the main obstacles to the effectiveness of village regulations. Mentoring activities play an important role in increasing the capacity of village apparatus and the Village Consultative Body (BPD) so that they are able to produce regulations that are legally valid, socially accepted, and responsive to community needs. These efforts contribute to the formation of participatory, transparent, and sustainable village governance systems, while providing a model that can be replicated in other villages to improve the quality of local governance.